KORELASI MOTIVASI BELAJAR BAHASA ARAB DENGANMINAT BERKOMUNIKASI DALAMBAHASA ARAB PADA MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB FAKULTAS TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAMNEGERI SULTAN SYARIF KASIM RIAU. - Mainizar N (Sosial Budaya, 2011)
This research backgrounded by its reducing gives a damn and its low majors college student ability PBA in gets communication with arabic, eventually Faculty and also Majors party have done various trick to increase it. Problem that is analyzed is: what and how motivates and arabic studying yen college student and what there is relationship which signifikan among motivates studying by give a damn to get communication in arabic?. To answer about problem this was gathered data via questionnaire to 80 respondents, then dianalisis with diskriptif, kualitatif with kontingensi's percentage and correlation. Its result points out that arabic learned motivation college student comes under tall with percentage 84,40 % meanwhile yen get rank communication high enough with percentage 78,80 %. But presentase both is not a far cry. analisis's result kontingensi's correlation points out no correlation which signifikan among motivate